Carnosine exhibits significant antiviral activity against Dengue and Zika virus. (9th July 2019) - Rothan, Hussin A.; Abdulrahman, Ammar Yasir; Khazali, Ahmad Suhail; Nor Rashid, Nurshamimi; Chong, Teoh Teow; Yusof, Rohana
Abstract : Dengue virus (DENV) and Zika virus (ZIKV) are flaviviruses transmitted to humans by their common vector, Aedes mosquitoes. DENV infection represents one of the most widely spread mosquito‐borne diseases whereas ZIKV infection occasionally re‐emerged in the past causing outbreaks. Although there have been considerable advances in understanding the pathophysiology of these viruses, no effective vaccines or antiviral drugs are currently available. In this study, we evaluated the antiviral activity of carnosine, an endogenous dipeptide (β‐alanyl‐l ‐histidine), against DENV serotype 2 (DENV2) and ZIKV infection in human liver cells (Huh7). Computational studies were performed to predict the potential interactions between carnosine and viral proteins. Biochemical and cell‐based assays were performed to validate the computational results. Mode‐of‐inhibition, plaque reduction, and immunostaining assays were performed to determine the antiviral activity of carnosine. Exogenous carnosine showed minimal cytotoxicity in Huh7 cells and rescued the viability of infected cells with EC50 values of 52.3 and 59.5 μM for DENV2 and ZIKV infection, respectively. Based on the mode‐of‐inhibition assays, carnosine inhibited DENV2 mainly by inhibiting viral genome replication and interfering with virus entry. Carnosine antiviral activity was verified with immunostaining assay where carnosine treatment diminished viral fluorescence signal. In conclusion, carnosine exhibited significant inhibitory effects against DENV2 and ZIKV replication in human liver cells and could be utilized as a lead peptide for the development of effective and safe antiviral agents against DENV and ZIKV. Abstract : Antiviral activities of carnosine against Dengue and Zika virus were investigated. Carnosine (magenta) was predicted to interact with the catalytic triad residues (yellow) of viral protease (cyan) and block viral protease activity leading to the inhibition of viral genome replication.